Interoperability Mechanism between Transport Enterprises and Educational Institutions in Operation of a Vehicle-Logistic Cluster - Ковбатюк, М.; Шевчук, В. (Київський національний університет імені Тараса Шевченка, 2018)
Запропоновано організаційно-економічний механізм взаємодії транспортних підприємств та освітніх установ у процесі функціонування транспортно-логістичного кластера. Механізм базується на моделі взаємодії між транспортними підприємствами й освітніми установами. Проведено порівняльний аналіз моделі взаємодії даних суб'єктів щодо їх входження у кластер та до складу кластерної структури. Визначено основні цілі функціонування досліджуваних суб'єктів транспортно-логістичного кластера, здійснено розподіл їх за рівнями та встановлено зв'язки між ними.

In the paper organizational economic mechanism of interaction between transport enterprises and higher education institutes in transport and logistics cluster has been suggested. This mechanism is based on the interaction model between transport enterprises and higher education institutes. New requirements for specialists on the transport services market cause the need for new relations formation between transport enterprises and higher education institutes. Therefore, training of highly specialized workers for transport and logistics cluster entities is possible only if there is effective interaction between enterprises and educational institutions. Comparative analysis of the interaction model was carried out between these entities before their entering to cluster and in cluster structure. It is defined that as a result of interaction between transport enterprises and higher education institutes in transport and logistics cluster, educational institutions could be supported by enterprises (funding, internship) and enterprises would hire qualified employees which level meets their needs. The study defined main goals of investigated objects in transport and logistics cluster, their distribution of the levels and establishment of links.
Механізм взаємодії транспортних підприємств та освітніх установ у процесі функціонування транспортно-логістичного кластера
Keywords: транспортно-логістичний кластер; транспортні підприємства; освітні установи; взаємодія суб'єктів кластера; організаційно-економічний механізм; transport and logistic cluster; transport enterprises; educational institutions; interaction of subjects of the cluster; organizational and economic mechanism